Effects of Tuina combined with aricular acupoint pressing therapy in the treatment of post-stroke constipation (便秘推拿联合耳穴压豆治疗中风后恢复期便秘临床效果观察) - LIU Wenli (刘文丽); GUO Haijiao (果海姣); SONG Ying (宋颖); SUI Yi (孙祎); GAO Jiajia (高佳佳); MA Xiaoxu (马晓旭); CHEN Cheng (陈程) (Association of Integrative Nursing, 2024)
Objective To investigate the effect of Tuina combined with auricular acupoint pressing therapy in the treatment of post-stroke constipation. Methods Totally 100 bedridden patients with post-stroke constipation were randomly divided in the observation group and control group, with 50 cases in each group. All patients received comprehensive treatment and routine nursing interventions, and those in the observation group were given Tuina combined with aricular acupoint pressing therapy. The intervention effect was evaluated and compared between two groups. Results The total effective rate was 94. 00%(47/50) in the observation, which was higher than 66. 00%(33/50) in the control group(P＜0. 05). Conclusion Tuina combined with aricular acupoint pressing therapy is effective to relive the symptoms of constipation in bedridden patients with post-stroke constipation. (目的 探讨便秘推拿联合耳穴压豆治疗中风后恢复期便秘的效果。方法 将100例卧床的中风后恢复期便秘患者随机分为观察组及对照组, 各50例。对照组实施常规护理干预, 观察组在对照组基础上增加便秘推拿联合耳穴压豆。评价两组干预效果。结果 观察组总有效率94. 00%(47/50), 高于对照组的66. 00%(33/50), 差异有统计学意义(P＜0. 05)。结论 对中风后恢复期患者采用便秘推拿配合耳穴压豆, 能进一步缓解便秘症状。)